Gut microbiota in systemic lupus erythematosus: A fuse and a solution - Chen, Yanfei; Lin, Jin; Xiao, Lanlan; Zhang, Xuan; Zhao, Lidan; Wang, Min; Li, Lanjuan (Journal of Autoimmunity, 2022)
Gut commensals help shape and mold host immune system and deeply influence human health. The disease spectrum of mankind that gut microbiome may associate with is ever-growing, but the mechanisms are still enigmas. Characterized by loss of self-tolerance and sustained self-attack, systemic lupus erythematosus (SLE) is labeled with chronic inflammation, production of autoantibodies and multisystem injury, which so far are mostly incurable. Gut microbiota and their metabolites, now known as important environmental triggers of local/systemic immune responses, have been proposed to be involved in SLE development and progression probably through the following mechanisms: translocation beyond their niches; molecular mimicry to cross-activate immune response targeting self-antigens; epitope spreading to expand autoantibodies spectrum; and bystander activation to promote systemic inflammation. Gut microbiota which varies between individuals may also influence the metabolism and bio-transformation of disease-modifying anti-rheumatic drugs, thus associated with the efficacy and toxicity of these drugs, adding another explanation for heterogenic therapeutic responses. Modulation of gut microbiota via diet, probiotics/prebiotics, antibiotics/phages, fecal microbiota transplantation, or helminth to restore immune tolerance and homeostasis is expected to be a promising neoadjuvant therapy for SLE. We reviewed the advances in this territory and discussed the application prospect of modulating gut microbiota in controlling SLE. •Systemic lupus erythematosus is characterized by loss of self-tolerance and sustained self-attack.•Gut microbiota and their metabolites have been proposed to be involved in SLE development and progression.•Gut microbiota may also influence the metabolism of disease-modifying anti-rheumatic drugs.•Modulation of gut microbiota to restore immune tolerance and homeostasis is a promising neoadjuvant therapy for SLE.